2017
DOI: 10.1038/ncomms15647
|View full text |Cite
|
Sign up to set email alerts
|

Compressional pathways of α-cristobalite, structure of cristobalite X-I, and towards the understanding of seifertite formation

Abstract: In various shocked meteorites, low-pressure silica polymorph α-cristobalite is commonly found in close spatial relation with the densest known SiO2 polymorph seifertite, which is stable above ∼80 GPa. We demonstrate that under hydrostatic pressure α-cristobalite remains untransformed up to at least 15 GPa. In quasi-hydrostatic experiments, above 11 GPa cristobalite X-I forms—a monoclinic polymorph built out of silicon octahedra; the phase is not quenchable and back-transforms to α-cristobalite on decompression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 58 publications
14
41
0
Order By: Relevance
“…For example in Martian meteorites, the shock pressure and temperature conditions (Fritz et al 2005a, 2005b) were found to be highly consistent with a thermal history inferred from a variety of independent properties, including (1) the radiogenic 4 He inventory (Schwenzer et al 2008), (2) the magnetic properties of ALH84001 (Weiss et al 2000); (3) the recrystallization of plagioclase in a decimeter-sized rock that cooled in space (Fritz et al 2005a), (4) the formation of seifertite enclosed in maskelynite in the Shergotty meteorite (Sharp et al 1999;Bl€ aß 2013;Kubo et al 2015;Cernok et al 2017; this work), and (5) the formation and preservation of thermally unstable high pressure phases associated with shock-produced melt veins and pockets in some meteorites (Fritz et al 2017;Tomioka and Miyahara 2017;Bischoff et al 2019). The low temperature solid state formation of maskelynite does not reset the 40 Ar-39 Ar chronometer of rocks, as Ar diffusion requires a prolonged heating regime (Jessberger and Ostertag 1982;Fernandes et al 2009;Shuster et al 2010).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…For example in Martian meteorites, the shock pressure and temperature conditions (Fritz et al 2005a, 2005b) were found to be highly consistent with a thermal history inferred from a variety of independent properties, including (1) the radiogenic 4 He inventory (Schwenzer et al 2008), (2) the magnetic properties of ALH84001 (Weiss et al 2000); (3) the recrystallization of plagioclase in a decimeter-sized rock that cooled in space (Fritz et al 2005a), (4) the formation of seifertite enclosed in maskelynite in the Shergotty meteorite (Sharp et al 1999;Bl€ aß 2013;Kubo et al 2015;Cernok et al 2017; this work), and (5) the formation and preservation of thermally unstable high pressure phases associated with shock-produced melt veins and pockets in some meteorites (Fritz et al 2017;Tomioka and Miyahara 2017;Bischoff et al 2019). The low temperature solid state formation of maskelynite does not reset the 40 Ar-39 Ar chronometer of rocks, as Ar diffusion requires a prolonged heating regime (Jessberger and Ostertag 1982;Fernandes et al 2009;Shuster et al 2010).…”
Section: Discussionsupporting
confidence: 54%
“…; Cernok et al. ; this work), and (5) the formation and preservation of thermally unstable high pressure phases associated with shock‐produced melt veins and pockets in some meteorites (Fritz et al. ; Tomioka and Miyahara ; Bischoff et al.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…2c), a few pronounced peaks become apparent. They coincide with vibrational signatures of the cristobalite 18 and tetragonal zirconia 19 phases, which are formed at high temperatures 20,21 . Figure 3 shows X-ray diffraction (XRD) data of annealed powder samples.…”
Section: Resultssupporting
confidence: 69%